Triblock copolymer nanovesicles for pH-responsive targeted delivery and controlled release of siRNA to cancer cells - Gallon, Elena; Matini, Teresa; Sasso, Luana; Mantovani, Giuseppe; Armiñan de Benito, Ana; Sanchis, Joaquin; Caliceti, Paolo; Alexander, Cameron; Vicent, Maria J.; Salmaso, Stefano (American Chemical Society, 2015)
New pH-responsive polymersomes for active anticancer oligonucleotide delivery were prepared from triblock copolymers. The delivery systems were formed by two terminal hydrophilic blocks, PEG and polyglycerolmethacrylate (poly-GMA), and a central weakly basic block, polyimidazole-hexyl methacrylate (poly-ImHeMA), which can complex with oligonucleotides and control vesicle formation/disassembly via pH variations. Targeted polymersomes were prepared by mixing folate-derivatized and underivatized copolymers. At pH 5, ds-DNA was found to complex with the pH-responsive copolymers at a N/P molar ratio above ∼2:1, which assisted the encapsulation of ds-DNA in the polymersomes, while low association was observed at pH 7.4. Cytotoxicity studies performed on folate receptor overexpressing KB and B16–F10 cells and low folate receptor expressing MCF-7 cells showed high tolerance of the polymersomes at up to 3 mg/mL concentration. Studies performed with red blood cells showed that at pH 5.0 the polymersomes have endosomolytic properties. Cytofluorimetric studies showed a 5.5-fold higher uptake of ds-DNA loaded folate-functional polymersomes in KB cells compared to nontargeted polymersomes. In addition, ds-DNA was found to be localized both in the nucleus and in the cytosol. The incubation of luciferase transfected B16–F10 cells with targeted polymersomes loaded with luciferase and Hsp90 expression silencing siRNAs yielded 31 and 23% knockdown in target protein expression, respectively.